Evaluation of Different Spray Frequency Levels of Fungicides against Ascochyta Blight (Ascochyta fabae S) Diseases of Faba Bean (Vicia faba L) in Northwestern Ethiopia - Habtu Tessema; Asefa Sintayehu; Zewdu Teshome; Teferi Alem (Advances in Agriculture)
Ascochyta blight disease is a major problem in faba bean (Vicia faba L) production that causes 90% to 100% yield loss. A field experiment was conducted to evaluate the efficacy of three fungicides with three spray frequency levels against Ascochyta blight disease of faba bean varieties. For the assessment of disease management, a total of 21 treatments were used, which comprised three fungicides, three spray frequencies, two varieties, and control. The field experiment was arranged in a randomized complete block design with factorial combinations of variety, fungicide, and spray frequency levels in three replications. An analysis of variance was performed for disease, yield, and yield related and plant growth parameter data, using the Statistical Analysis System (SAS, 2003) version 9.1.3 software. The economic data obtained from the field experiment was analyzed using the partial budget analysis method. The results showed that area under disease progress curve, percent severity index, disease progress rate, and percent disease incidence had strong mean significant differences (p<0.01) between treated and untreated plots. Application of fungicide significantly increased plant height, stem girth, pod per plant, grain yield, and harvesting index (p<0.01) over untreated plots. Greater total return (195,938 Ethiopian birr ha−1), net return (101,761.3 Ethiopian birr ha−1), and net benefit (34,768.17 Ethiopian birr ha−1) were obtained by EH00102-4-1 variety, in two times Mancolaxyl treatment. The linear regression analysis result (R2) indicated that the variation in average grain yield of EH00102-4-1 and local susceptible varieties, due to the mean area under the disease progress curve, was 64.50% and 68.64%, respectively. Therefore, the use of EH00102-4-1 variety, with two times Mancolaxyl spray frequency application, at early growth stage and the onset of the disease is suggested as an agronomic management option, in Northwestern Ethiopia.